Pengaruh Pemasaran Afiliasi E-Commerce pada Media Sosial Terhadap Minat Beli Mahasiswa Politeknik Negeri Bandung - Rena Puspitasari (Asosiasi Ahli Administrasi Indonesia, 2023)
The purpose of this study was to determine the effect of e-commerce affiliate marketing on social media on the buying interest of Bandung State Polytechnic students. The sample used in this study was 108 respondents who were Bandung State Polytechnic students who had or often saw e-commerce affiliate marketing content on social media. This research uses descriptive analysis method, validity test, reliability test, correlation analysis and simple regression analysis. Data collection was carried out through questionnaires distributed via social media to respondents who met the criteria. In this study, the results obtained were 66.7% of the influence of e-commerce affiliate marketing on purchase intention. Meanwhile, 33.3% is influenced by other variables not discussed in this study. The results of this study indicate that e-commerce affiliate marketing has influence and its influence is included in the low criteria.